2016
DOI: 10.1080/15377938.2016.1187236
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic diversity in policing: An application of quantile regression to the New York City Police Department

Abstract: This study expanded on the use of Simpson's diversity index (D = 1 -∑p 2 ) to measure ethnic heterogeneity in policing and other criminal justice-related agencies. The index was applied to the police and civilian workforces of the New York City Police Department (NYPD) by using employment data for January 2015. Concomitantly, quantile regression was used to supplement the Tobit regression and to illustrate its ability to assess the effects of organization-based variables across the conditional distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The number of parameters obtained was intentionally limited to three of the most informative for each determinant. From the majority of the publications examined, the basis for the selection of the respective parameters formed (Ahlf et al, 2019), (Allen et al, 2007), (Bansal et al, 2017), (Bischoff, 2016), (Demigha, 2021), (Guajada, 2016), (Hermann, 2019), (Ilseven & Puranam, 2021), (Lamb, 2020) In addition to these determinants resulting from the publication and network analyses, organisational characteristics were included as they are useful for further research and surrogate model building. The dependencies of individual determinants and parameters among each other are not clear from the relation of the surrogate model.…”
Section: Methodology and Research Resultsmentioning
confidence: 99%
“…The number of parameters obtained was intentionally limited to three of the most informative for each determinant. From the majority of the publications examined, the basis for the selection of the respective parameters formed (Ahlf et al, 2019), (Allen et al, 2007), (Bansal et al, 2017), (Bischoff, 2016), (Demigha, 2021), (Guajada, 2016), (Hermann, 2019), (Ilseven & Puranam, 2021), (Lamb, 2020) In addition to these determinants resulting from the publication and network analyses, organisational characteristics were included as they are useful for further research and surrogate model building. The dependencies of individual determinants and parameters among each other are not clear from the relation of the surrogate model.…”
Section: Methodology and Research Resultsmentioning
confidence: 99%
“…Articles assessing workforce diversity centered on evaluations comprised of studies specific to cities/geographic areas and/or nationally derived evaluations. Comparing the NYPD to the overall civilian population, Guajardo () found that minority representation is conditional on the level of assessment, but overall minority representation within the NYPD is less diverse than the general civilian workforce. The level of diversity within the NYPD police ranks declines precipitously and consistently after the rank of sergeant, and the disparity ratios reveal that the number of White officers far exceeds that of Black, Hispanic, Asian, and other minority group officers for all remaining ranks (Guajardo, ).…”
Section: Resultsmentioning
confidence: 99%
“…The value of D ranges between 0 and 1 with 1 representing infinite diversity and 0, no diversity. The index has been commonly employed in the criminological literature to examine a range of topics ranging from the impacts of diversity on burglary crime (Gulma et al, 2019) to ethnic diversity in policing (Guajardo, 2016). Morris and Worrall (2014) also developed a gang composition index reflecting the diversity of prison gangs in their research examining the effect of prison architecture on inmate misconduct in prisons in Texas.…”
Section: Gang Membershipmentioning
confidence: 99%